Analisis Perlindungan Hukum Bagi WNI yang Berwisata Religi ke Negara Israel - Gracianto, Hubertus Divo; Fathinnuddin, Muhammad (Postulat, 2025)
This research focuses on the legal protection for Indonesian tourists undertaking religious journeys to Israel, a country that does not have diplomatic relations with Indonesia. The author's experience in guiding tourists to Israel raises concerns about the security and legal certainty they face while there. This study analyzes two main issues: (1) the bilateral relationship between Indonesia and Israel in the context of international law and the tourism industry, and (2) the responsibilities and legal protections provided by the Indonesian government to Indonesian citizens (WNI) as tourists in a country without official diplomatic relations. The research method employed is normative legal research, utilizing an approach to relevant regulations, concepts, and legal cases. This study aims to produce conclusions regarding: (1) the regulation of state responsibilities in bilateral contexts and the protection of WNI by the Ministry of Tourism through travel agents and local service providers, and (2) recommendations for formulating legal products that can ensure protection for WNI as foreign tourists in the country. Although some legal instruments have been outlined in regulations through the Indonesian embassy in nearby countries, there remains a normative vacuum that needs to be addressed. Therefore, a consensus or legal agreement between local service providers and service users is necessary to prevent losses arising from issues, disputes, or circumstances beyond control (force majeure).